ECONOMICS OF MILK PRODUCTION : A CASE STUDY OF AJMER DISTRICT CO-OPERATIVE MILK PRODUCERS’ UNION (Indian Journal of Animal Production and Management, 2013)
The present study was taken up to study the socio-economic conditions of the milk producers and to work out the seasonal cost ansd returns from milk production in the milk shed area of Ajmer District Co-operative Milk Producers’ Union. The study was based on 312 milk producing households (comprising 104 in each season) comprising of 60 small, 31 medium and 13 large households which were selected randomly from two societies i.e. Jethana and Bandarsendri with probality proportional to size of herd in each category. In the study area dairy farming was main occupation of about 12 percent farmers. The average herd size is 4.92 milch animals which comprises of 2.64 buffaloes, 1.61 local cow and 0.67 for crossbred cows. The per day maintenance cost of milch buffalo was found to be higher (Rs. 69.42) in comparison to crossbred cows (Rs. 56.81) and local cows (Rs. 55.21). The maintenance cost varied in different seasons and found to be the highest in winter season ands lowest in rainy season for all types of animals. By and large, variable cost constituted 86.74 percent in buffalo, 91.61 percent for local cows and 88.9 percent in crossbreds. The cost per litre of milk production in buffalo was Rs. 14.99, 10.20, 13.09 and 12.76 for summer, rainy, winter and overall respectively. In crossbred cow, the cost per litre of milk production for summer, rainy, winter and overall was found to be Rs. 111.02, 8.37, 10.24 and 9.86, respectively while in local cow the corresponding cost was 13.25, 8.16, 12.41 and 11.27. Net return per litre of was Rs. 0.12, 1.90, 0.12 and 0.73 for summer, rainy, winter and overall in crossbred cow, respectively. This net return was more in buffalo, where it was Rs. 3.56, 7.38, 6.06 and 5.67 for summer, rainy, winter and overall, whereas in local cow per litre net return was Rs. 0.39, 4.38, 1.41 and 1.80 for summer, rainy, winter and overall respectively. In the study area, the highest milk price was paid for buffalo followed by loocal cow and crossbred cow.
Keywords: Cost of milk production; Dairy Co-operative; Economics; Ajmer